The relationship between neighborhood socioeconomic deprivation and telomere length: The 1999–2002 National Health and Nutrition Examination Survey. (April 2020) - Powell-Wiley, Tiffany M.; Gebreab, Samson Y.; Claudel, Sophie E.; Ayers, Colby; Andrews, Marcus R.; Adu-Brimpong, Joel; Berrigan, David; Davis, Sharon K.
Abstract: Socioeconomically disadvantaged neighborhoods have been associated with poor health outcomes. Little is known about the biological mechanism by which deprived neighborhood conditions exert negative influences on health. Data from the 1999–2002 National Health and Nutrition Examination Surveys (NHANES) were used to assess the relationship between neighborhood deprivation index (NDI) and log-transformed leukocyte telomere length (LTL) via multilevel modeling to control for census tract level clustering. Models were constructed using tertiles of NDI (ref = low NDI). NDI was calculated using census tract level socioeconomic indicators from the 2000 U.S. Census. The sample (n = 5, 106 adults) was 49.8% female and consisted of 82.9% non-Hispanic whites, 9.4% non-Hispanic blacks, and 7.6% Mexican Americans. Mean age was 45.8 years. Residents of neighborhoods with high NDI were younger, non-white, had lower educational attainment, and had a lower poverty to income ratio (all p  < 0.0001). Neighborhood deprivation was inversely associated with LTL among individuals living in neighborhoods with medium NDI (β = −0.043, SE = 0.012, p  = 0.0005) and high NDI (β = −0.039, SE = 0.013, p  = 0.003). Among men, both medium (β = −0.042, SE = 0.015, p  = 0.006) and high (β = −0.047, SE = 0.015, p  = 0.001) NDI were associated with shorter LTL. Among women, only medium NDI (β = −0.020, SE = 0.016, p  = 0.009) was associated with shorter LTL. After controlling for individual characteristics, including individual-level socioeconomic status, increasing neighborhood socioeconomic deprivation is associated with shorter LTL among a nationally representative sample of US adults. This suggests that telomere shortening may be a mechanism through which neighborhood deprivation results in poor health outcomes. Highlights: Neighborhood deprivation is inversely related to telomere length. This persists after adjusting for behavior and individual socioeconomic status. Telomere shortening in high deprivation represented 7.5 years of accelerated aging. Telomere shortening may be a mechanism linking neighborhoods and health.